Studi Etnofarmasi Suku Kaili Moma Di Kecamatan Kulawi, Kabupaten Sigi, Provinsi Sulawesi Tengah: Ethnomedicinal Study of Kaili Moma Tribe In Kulawi Subdistrict, Sigi Regency, Central Sulawesi - Muhammad Yusuf Islami; Nurlina Ibrahim; Arsa Wahyu Nugrahani (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2017)
This study aims to inventory and to know the ways of utilization as well as parts of the plants which have been used by people of Kaili Moma Tribe in Kulawi Subdistrict, Sigi Regency, Central Sulawesi. This research is a descriptive study which used qualitative methods and purposive sampling technique through open-ended interviews to 87 people of Kaili Moma Tribe using questionnaire. The results of this study showed that there were 51 species of plants, classified into 29 familia, used as remedies (traditional medicine) for the treatments of 41 types of disease. The most widely used plants came from family Lamiaceae with percentage of 17%. The parts of plant used by the people included leaves, fruits, stems, tubers, roots, rhizomes, seeds, herbs, flowers and thorns. Part of the plants most frequently used as remedies is leaf with percentage of 49%. Ways of the plants utilization were very diverse, such as boiling; squeezing, and pounding. The people use them in ways of drinking, eating, rubbing, and affixing them to the affected part.